Development of Multi-Tee-Type Precast Concrete Slabs with Insulating Materials for Structural Safety at the Construction Stage - Jang-Woon Baek; Su-Min Kang (Applied Sciences, 2021)
Multi-tee-type precast concrete (PC) slab systems are widely used for the construction of modular high-load long-span buildings. However, the structural safety of the dapped end is uncertain, owing to the unanchored shear reinforcement at the construction stage. This study proposes the use of clip-type shear reinforcement at the dapped ends of multi-tee PC slabs to secure their structural performance at the construction stage. To investigate the performance of this approach, a monotonic loading test was performed on simply supported PC slabs, considering structural safety at the construction stage. The reinforcement details of the PC slab’s dapped end (with existing Z-type or proposed clip-type shear reinforcement) and the shear-to-span ratio (12.8 or 6.4) were considered as test parameters. The load–deflection relationship, failure mode, strength ratios to the predicted strength, and shear reinforcement strains were analyzed. The results showed that the tested flexural strength ratio of the PC slabs at the construction stage to the design flexural strength was 1.20–1.40. The enclosed shape and diagonal arrangement of the clip-type shear reinforcement enabled sufficient anchorage performance at the dapped end, indicating that clip-type shear reinforcement can be viable for use at the dapped ends of PC slabs under construction loads.